A Top‐Down Strategy to Engineer ActiveLayer Morphology for Highly Efficient and Stable All‐Polymer Solar Cells. Issue 33 (15th July 2022) - Fu, Huiting; Peng, Zhengxing; Fan, Qunping; Lin, Francis R.; Qi, Feng; Ran, Yixin; Wu, Ziang; Fan, Baobing; Jiang, Kui; Woo, Han Young; Lu, Guanghao; Ade, Harald; et al.
Abstract: A major challenge hindering the further development of all‐polymer solar cells (all‐PSCs) employing polymerized small‐molecule acceptors is the relatively low fill factor (FF) due to the difficulty in controlling the active‐layer morphology. The issues typically arise from oversized phase separation resulting from the thermodynamically unfavorable mixing between two macromolecular species, and disordered molecular orientation/packing of highly anisotropic polymer chains. Herein, a facile top‐down controlling strategy to engineer the morphology of all‐polymer blends is developed by leveraging the layer‐by‐layer (LBL) deposition. Optimal intermixing of polymer components can be achieved in the two‐step process by tuning the bottom‐layer polymer swelling during top‐layer deposition. Consequently, both the molecular orientation/packing of the bottom layer and the molecular ordering of the top layer can be optimized with a suitable top‐layer processing solvent. A favorable morphology with gradient vertical composition distribution for efficient charge transport and extraction is therefore realized, affording a high all‐PSC efficiency of 17.0% with a FF of 76.1%. The derived devices also possess excellent long‐term thermal stability and can retain >90% of their initial efficiencies after being annealed at 65 °C for 1300 h. These results validate the distinct advantages of employing an LBL processing protocol to fabricate high‐performance all‐PSCs. Abstract : A facile top‐down strategy to control the all‐polymer solar cell (all‐PSC) morphology is developed by layer‐by‐layer processing. Optimal intermixing of polymer components and improved molecular packing of bottom layer and top layer can be achieved by choosing a suitable top‐layer processing solvent. Consequently, a favorable morphology with gradient vertical composition distribution is realized, affording a high all‐PSC efficiency of 17.0%.